ナンキョク アスカ カンソク キョテン ニ オケル アイスドーム ノ セイサク - 石沢, 賢二; イシザワ, ケンジ; 粉川, 牧; コカワ, ツトム; 半貫, 敏夫; ハンヌキ, トシオ; Ishizawa, Kenji; Kokawa, Tsutomu; Hannuki, Toshio (1993)
P(論文) アイスドームの製作技術と時間によるその変形を研究するために, アイスドームの建設が試みられた。直径10mの膜を送風機で膨らませ, 水と雪をこの上にかけた。約13tの水を使って厚さ7cm, 高さ3mのものができあがった。天井はクリープにより, 徐々に変形が進み, 中央部は99日間で55mm沈下した。また, 夏にはアイスドームの厚さが昇華により急速に薄くなったため, ロータリ除雪車で時々雪掛けを行った。このアイスドームは倉庫あるいは作業場として有効に使用できた。もうひとつのアイスドームは, このために持ち込んだ造水装置を使用して実施したが, 強風と低温で大変な作業だった。また, 水を使わない雪だけのスノードームの製作も試みたが, 固まらなかった。 An attempt was made to construct an ice dome in order to study the construction technique and to examine its deformation by creep and sublimation of ice in the Antarctic. A 10-m diameter membrane was inflated by a ventilator. Stored water was sprayed on it, and sometimes milled snow was blown by a small snow miller. About 13t of water was consumed for making an ice dome 7cm thick, 3m high. The deformation of the ceiling grew with time due to creep. The sinkage of the center reached 55mm after 99 days. The wall thickness rapidly decreased due to sublimation in summer time; consequently, snow was occasionally added with a rotary snowplow. The ice dome was effectively used as storehouse and workshop. Though it was attmpted to make water outside by using a snow melter with an oil burner for another ice dome, the work was hard. A snow dome without water was also attempted, but the snow did not harden. departmental bulletin paper